Dominant negative (ΔN) p63α induces drug resistance in hepatocellular carcinoma by interference with apoptosis signaling pathways - Mundt, Heiko; Stremmel, Wolfgang; Melino, Gerry; Krammer, Peter H.; Schilling, Tobias; Müller-Schilling, Martina (Biochemical and biophysical research communications, 2010)
p63 belongs to the family of p53-related transcription factors expressing a variety of isoforms. The Trp63 gene has two promoters that drive the expression of two major p63 isoform subfamilies. Isoforms of the TAp63 subfamily show pro-apoptotic activities, whereas members of the N-terminally truncated (ΔN) p63 subfamily have anti-apoptotic functions. We have previously shown an important role for TAp63α in the induction of apoptosis and chemosensitivity of hepatocellular carcinoma (HCC). Here, we investigated the molecular mechanisms accounting for the oncogenic role of ΔNp63α in HCC. ΔNp63α can directly interfere with the transcriptional activation function of the TA (containing the transactivation domain) isoforms of the p53 family and consequently inhibit transactivation of pro-apoptotic target genes. ΔNp63α negatively regulates the genes encoding for the death receptor CD95 and the pro-apoptotic Bcl-2 family member BAX. Thus, ΔNp63α expression in HCC interferes with both the death receptor and the mitochondrial apoptosis activity of the TA isoforms. In addition and of clinical relevance, ΔNp63α inhibits activation of p53 family target genes and apoptosis induced by chemotherapeutic drugs. Chemotherapeutic treatment induces expression of Bax, Bim, Noxa, Puma and Perp; this is antagonized by ΔNp63α. Our data suggest that the ΔNp63α isoform represses apoptosis-related genes of the extrinsic and intrinsic apoptosis signaling pathways, thereby contributing to chemoresistance of HCC.